Outcomes of the CT2 study: A 'one‐stop‐shop' for community‐based hepatitis C testing and treatment in Yangon, Myanmar. (10th July 2021) - Draper, Bridget Louise; Htay, Hla; Pedrana, Alisa; Yee, Win Lei; Howell, Jessica; Pyone Kyi, Khin; Naing, Win; Sanda Aung, Khin; Markby, Jessica; Easterbrook, Philippa; Bowring, Anna; Aung, Win; et al.
Abstract: Background: With the advent of low‐cost generic direct‐acting antivirals (DAA), hepatitis C (HCV) elimination is now achievable even in low‐/middle‐income settings. We assessed the feasibility and effectiveness of a simplified clinical pathway using point‐of‐care diagnostic testing and non‐specialist‐led care in a decentralized, community‐based setting. Methods: This feasibility study was conducted at two sites in Yangon, Myanmar: one for people who inject drugs (PWID), and the other for people with liver disease. Participants underwent on‐site rapid anti‐HCV testing and HCV RNA testing using GeneXpert (R) . General practitioners determined whether participants started DAA therapy immediately or required specialist evaluation. Primary outcome measures were progression through the HCV care cascade, including uptake of RNA testing and treatment, and treatment outcomes. Findings: All 633 participants underwent anti‐HCV testing; 606 (96%) were anti‐HCV positive and had HCV RNA testing. Of 606 tested, 535 (88%) were RNA positive and had pre‐treatment assessments; 30 (6%) completed specialist evaluation. Of 535 RNA positive participants, 489 (91%) were eligible to initiate DAAs, 477 (98%) completed DAA therapy and 421 achieved SVR12 (92%; 421/456). Outcomes were similar by site: PWID site: 91% [146/161], and liver disease site: 93% [275/295]). Compensated cirrhotic patients were treated in the community; they achieved an SVR12 of 83% (19/23). Median time from RNA test to DAA initiation was 3 days (IQR 2‐5). Conclusions: Delivering a simplified, non‐specialist‐led HCV treatment pathway in a decentralized community setting was feasible in Yangon, Myanmar; retention in care and treatment success rates were very high. This care model could be integral in scaling up HCV services in Myanmar and other low‐ and middle‐income settings.